Facilitating educational contents of different subjects with context-agnostic educational game: A pilot case study - Atmaja, Pratama Wirya; Muttaqin, Faisal; Sugiarto, Sugiarto (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2020)
Educational games are increasingly popular and successful in facilitating various subjects and educational topics. Developing the games are often costly as the developers need to develop specific game content to facilitate each different educational content. One solution to the cost problem is the context-agnostic approach, which allows a game to facilitate educational contents of different subjects or educational topics with zero or minimal modifications to its game content. However, researches on the approach are still scarce, including those aimed at examining real-world applications of the approach. This case study was intended to fill the research gap by examining the application of a context-agnostic educational platformer game in a higher education scenario. The game was used to present educational contents of binary number system and ASCII codes, where both are taught in Informatics Engineering Department. The game was context-agnostic because it was able to flexibly assign educational content elements to various objects in its gameplay. Activity Theory-based Model of Serious Games (ATMSG) was used to guide the design of our educational game. The experiment was conducted with the participation of 60 first-year students of Informatics Engineering Department. The results show that the game can facilitate a more fun and engaging class session for the two educational topics without requiring any changes to the game content. The implication of the results and the implementation complexity of the context-agnostic approach are also discussed.